2019
DOI: 10.1002/cptc.201900084
|View full text |Cite
|
Sign up to set email alerts
|

Design of Two‐Photon‐Excited Fluorescent Dyes Containing Fluoroborylene Groups

Abstract: Aiming at establishing structure-property relationships for twophoton absorption, we present the results of an in silico investigation of dyes containing fluoroborylene (BF) groups. More specifically, we analyze the electronic properties corresponding to the one-and two-photon excitation to two lowestlying singlet states (S 1 and S 2 ) using TD-DFT and CC2 methods. BF-and BF 2 -containing fluorescent dyes are in the limelight, but it remains challenging to reach the larger electronic two-photon transition stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…This is indeed an extremely desirable feature for fluorescent dyes, as it leads to negligible overlapping of absorption and emission spectra, which in turn, prevents the emitted photons from being reabsorbed, a phenomenon that often plagues the applications of emissive dyes in biological media as well as in materials. It should be highlighted that electronic structure theories can provide valuable insight into the absorption and emission of radiation, enabling a deep understanding of excited-state properties [77][78][79][80][81][82], which are of pivotal importance for applications in many technological sectors. Indeed, the calculations of the excited-state properties are performed not only to gain insight into absorption, fluorescence, and phosphorescence processes, but also to model the fundamental aspects of energy conversion phenomena, such as those exploited in solar cells [83][84][85][86][87][88][89].…”
Section: Introductionmentioning
confidence: 99%
“…This is indeed an extremely desirable feature for fluorescent dyes, as it leads to negligible overlapping of absorption and emission spectra, which in turn, prevents the emitted photons from being reabsorbed, a phenomenon that often plagues the applications of emissive dyes in biological media as well as in materials. It should be highlighted that electronic structure theories can provide valuable insight into the absorption and emission of radiation, enabling a deep understanding of excited-state properties [77][78][79][80][81][82], which are of pivotal importance for applications in many technological sectors. Indeed, the calculations of the excited-state properties are performed not only to gain insight into absorption, fluorescence, and phosphorescence processes, but also to model the fundamental aspects of energy conversion phenomena, such as those exploited in solar cells [83][84][85][86][87][88][89].…”
Section: Introductionmentioning
confidence: 99%
“…In order to link the changes in two-photon S 0 → S 2 transition strengths for the series D1′, D2′, D2A′, and D4′ with electronic-structure parameters, we employed a generalized few-state model (GFSM; eq 8 of ref ). The analysis of S 0 → S 2 transition shows that, for all 4 molecules, it has the very same orbital character and is dominated by HOMO–1 → LUMO transition.…”
Section: Resultsmentioning
confidence: 99%
“…The functionals with fixed amount of exact exchange (e.g., B3LYP) fail to consistently predict key parameters, such as the transition moments between electronic states and excitation energies, so that their agreement with RI-CC2 reference data is due to error cancellations . Moreover, although range-separated functionals yield TPA strengths, which substantially deviate from reference values, the corresponding errors are rather systematic and these functionals nicely reproduce the chemical trends . To sum up, global hybrids provide more accurate orders of magnitude for TPA transition strengths, but less consistent chemical ranking.…”
Section: Methodsmentioning
confidence: 95%
See 1 more Smart Citation
“…In order to assess the effect of the heteroatom position in diazine-carrying donor−acceptor dyes on the TPACS values, we focus in this Letter on the compounds shown in Scheme 1, which also indicates atom numbering, the synthetic path, and the trans and cis forms. Previously, we have shown that BF 2carrying molecules based on amides exhibit significant twophoton absorption 20,21 and that the most effective were molecules with strong CT character. We stress that only one (or zero as in 1) colored nitrogen atom is present in a given molecule, so the changes are indeed minimal from one dye to another.…”
mentioning
confidence: 99%